Cerebellar and basal ganglia structural connections in humans: Effect of aging and relation with memory and learning - Radhakrishnan, Vineeth; Gallea, Cecile; Valabregue, Romain; Krishnan, Syam; Kesavadas, Chandrasekharan; Thomas, Bejoy; James, Praveen; Menon, Ramshekhar; Kishore, Asha (Frontiers in Aging Neuroscience, 2023)
Cerebellum and basal ganglia were initially considered anatomically distinct regions, each connected via thalamic relays which project to the same cerebral cortical targets, such as the motor cortex. In the last two decades, transneuronal viral transport studies in non-human primates showed bidirectional connections between the cerebellum and basal ganglia at the subcortical level, without involving the cerebral cortical motor areas. These findings have significant implications for our understanding of neurodevelopmental and neurodegenerative diseases. While these subcortical connections were established in smaller studies on humans, their evolution with natural aging is scarcely understood. Here, we validated and expanded the previous findings of the structural connectivity within the cerebellum-basal ganglia subcortical network in a larger dataset of 64 subjects across different age ranges. Tractography and fixel-based analysis were performed on 3T diffusion-weighted dataset using Mrtrix3 software, considering fiber density and cross-section as indicators of axonal integrity. Tractography of the well-established cerebello-thalamocortical tract was conducted as a control. We tested the relationship between the structural white matter integrity of these connections with aging and with performance in different domains of Addenbrooke’s Cognitive Examination. Tractography analysis isolated connections from the dentate nucleus to the contralateral putamen via the thalamus, and reciprocal tracts from the subthalamic nucleus to the contralateral cerebellar cortex via the pontine nuclei. Control tracts of cerebello-thalamo-cortical tracts were also isolated, including associative cerebello-prefrontal tracts. A negative linear relationship was found between fiber density of reciprocal cerebellum-basal ganglia tracts and age. Considering the cognitive assessments, the fibre density values of cerebello-thalamo-putaminal tracts correlated with the registration/learning domain scores. In addition, the fibre density values of cerebello-frontal and subthalamo-cerebellar (CrusII) tracts correlated with the cognitive assessment scores from the memory domain. In conclusion, structural features of subcortical cerebello-basal ganglia tracts in human subjects display age-related neurodegeneration. Individual morphological variability of cerebellar tracts to the striatum and prefrontal cortex was associated with different cognitive functions, suggesting a functional contribution of cerebellar tracts to cognitive decline with aging. This study offers new perspectives to consider the functional role of these pathways in motor learning and the pathophysiology of movement disorders involving the cerebellum and striatum.